1996
DOI: 10.1021/jf960257+
|View full text |Cite
|
Sign up to set email alerts
|

Natural Co-occurrence of Fumonisins and Zearalenone in Cereals and Cereal-Based Foods from Eastern and Southern Africa

Abstract: The natural co-occurrence of fumonisin B1 (FB1), fumonisin B2 (FB2), fumonisin B3 (FB3), and zearalenone was investigated in 40 randomly selected cereals and cereal-based commodities collected in 1994 from Botswana, Kenya, Malawi, Mozambique, South Africa, Tanzania, Uganda, Zambia, and Zimbabwe. FB1 was detected in 37 of the samples (92.5%) at concentrations ranging from 20 to 1910 ng/g, while total fumonisin (FB1 + FB2 + FB3) concentrations in the same samples ranged from 20 to 2735 ng/g. The highest total fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
2
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(53 citation statements)
references
References 28 publications
5
45
2
1
Order By: Relevance
“…This result was similar to the studies carried out by Soares and Rodriguez-Amaya (45) Zearalenone has been found in maize in many parts of the world (10,29,40,47). It is notorious that countries with hot climate have not been presented problems concerned to contamination by ZEA with maize.…”
Section: Resultssupporting
confidence: 91%
“…This result was similar to the studies carried out by Soares and Rodriguez-Amaya (45) Zearalenone has been found in maize in many parts of the world (10,29,40,47). It is notorious that countries with hot climate have not been presented problems concerned to contamination by ZEA with maize.…”
Section: Resultssupporting
confidence: 91%
“…As with China, there has been a modest change in the ratio of maize production to that of the other staple crops (sorghum, millet, rice). However, of these, maize is uniquely susceptible to fumonisin, DON and zearalenone and co-exposures with aflatoxin are certainly common (Doko et al 1996;Ngoko et al 2001) Africa has become extremely vulnerable to exposure from mycotoxins found in maize (Riley and Miller 2003;Azziz-Baumgartner et al 2005). China is producing sufficient food for residents of rural areas to purchase food (Gale et al 2005), which means that diets are much more diverse in China compared to Africa.…”
Section: Exposure To Maize and Wheat Borne Toxins Is Increasingmentioning
confidence: 99%
“…[101][102][103][104][105][106][107][108][109]. Poultry feed investigated in china was contaminated with 1854.3mg/kg (37).…”
Section: Occurrence Of Fumonisinmentioning
confidence: 99%